2010
DOI: 10.1103/physrevb.81.195216
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic point defects in aluminum antimonide

Abstract: We investigate thermodynamic and electronic properties of group IV (C, Si, Ge, Sn) and group VI (O, S, Se, Te) impurities as well as P and H in aluminum antimonide (AlSb) using first-principles calculations. To this end, we compute the formation energies of a broad range of possible defect configurations including defect complexes with the most important intrinsic defects. We also obtain relative scattering cross strengths for these defects to determine their impact on charge carrier mobility. Furthermore, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…We present results for a representative test case of a range of impurities in the zinc-blende semiconductor AlSb. 13,19 We have computed the values of the scattering matrix elements ͗f͉⌬V͉i͘ for a variety of relevant scattering channels throughout the Brillouin zone and also the corresponding relative scattering rates M 2 from Eq. ͑4͒ for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…We present results for a representative test case of a range of impurities in the zinc-blende semiconductor AlSb. 13,19 We have computed the values of the scattering matrix elements ͗f͉⌬V͉i͘ for a variety of relevant scattering channels throughout the Brillouin zone and also the corresponding relative scattering rates M 2 from Eq. ͑4͒ for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…These extrinsic point defects are chosen because they act as acceptors in AlSb and their formation energies were found to be the lowest ones for carbon and oxygen impurities in AlSb (Ref. 13).…”
Section: Methodsmentioning
confidence: 99%
“…The prediction of the Sb Ga donor levels associated with low defect formation energies is a challenge for explaining the Even though our main focus is on the native point defects, we also perform a very limited study of extrinsic point defects, namely carbon at the substitutional Sb site and oxygen at the interstitial cation site as possible sources of p-type conductivity. Erhart et al 13 studied these defects in AlSb and found them as the most detrimental impurities that can be unintentionally incorporated during the growth process. They used the LDA functional and 64-atom supercell to study various extrinsic point defects in AlSb and found that substitutional carbon at the Sb site acts as a singly acceptor for the whole range of the Fermi level.…”
Section: Introductionmentioning
confidence: 99%
“…At thermodynamic equilibrium, the concentration of each type of defect follows the Boltzmann distribution [40]:…”
Section: Scintillation Propertymentioning
confidence: 99%